A Phase II Trial of Pazopanib in Patients with Metastatic Alveolar Soft Part Sarcoma. (25th September 2018) - Kim, Miso; Kim, Tae Min; Keam, Bhumsuk; Kim, Yu Jung; Paeng, Jin Chul; Moon, Kyung Chul; Kim, Dong‐Wan; Heo, Dae Seog
Abstract: Lessons Learned: Pazopanib shows a modest efficacy in metastatic alveolar soft part sarcoma. Clinical outcomes were comparable to those in previous studies using antiangiogenic drugs. Further prospective studies evaluating the benefit of pazopanib in alveolar soft part sarcoma with a larger sample are warranted to validate results. Background: Alveolar soft part sarcoma (ASPS) is a rare mesenchymal malignant tumor characterized by an unbalanced translocation, t(X;17)(p11.2;q25), which leads to the fusion of ASPSCR1 to the TFE3 transcription factor. Because this results in the upregulation of angiogenesis‐related transcripts, antiangiogenic drugs have been used in ASPS patients. Methods: This open‐label, single‐arm, multicenter, investigator‐initiated phase II trial was designed to evaluate efficacy and safety of pazopanib 800 mg once daily in patients with metastatic ASPS. The primary endpoint was investigator‐assessed overall response rate (ORR), and secondary endpoints were toxicity, progression‐free survival (PFS), and overall survival (OS). 68 Ga‐RGD (Arg‐Gly‐Asp) positron emission tomography (PET) scan and gene expression profiling using NanoString platform were performed for biomarker analysis. Results: Six patients with histologically confirmed metastatic ASPS were enrolled between December 2013 and November 2014. Among six patients, one achieved a partial response (PR) (ORR 16.7%) and five patients showed stable disease (SD). With a median follow‐up of 33 months (range 18.7–39.3 months), median PFS was 5.5 months (95% confidence interval [CI] 3.4–7.6 months), and median OS was not reached. There were no severe toxicities except one patient with grade 3 diarrhea. Conclusion: Pazopanib showed modest antitumor activity with manageable toxicities for patients with metastatic ASPS.